Identification of MicroRNA-92a-3p as an Essential Regulator of Tubular Epithelial Cell Pyroptosis by Targeting Nrf1 via HO-1 - Wang, Renhe; Zhao, Haijun; Zhang, Yingyu; Zhu, Hai; Su, Qiuju; Qi, Haiyan; Deng, Jun; Xiao, Chengcheng (Frontiers in Genetics, 2021)
Renal ischemia-reperfusion injury (IRI) is a major cause of acute kidney injury (AKI), and no effective treatment is available. Exploring the molecular mechanisms of renal IRI is critical for the prevention of AKI and its evolution to chronic kidney disease(CKD) and end-stage renal disease(ESRD). The aim of the present study was to determine the biological function and molecular mechanism of action of miR-92a-3p in tubular epithelial cell(TEC) pyroptosis. We investigated the relationship between Nrf1 and TEC pyroptosis induced by ischemia-reperfusion (IR) in vivo and oxygen-glucose deprivation/reoxygenation (OGD/R) in vitro. MicroRNAs (miRNAs)are regulators of gene expression and play a role in the progression of renal IRI. Nrf1 was predicted to be and confirmed as a potential target for miRNA (miR)-92a-3p. In addition, the inhibition of miR-92a-3p alleviated oxidative stress in vitro and decreased the expression levels of NLRP3, caspase-1,GSDMD-N, IL-1β, and IL-18 in vitro and in vivo. Moreover, Zn-protoporphyrin-IX (ZnPPIX), an inhibitor of HO-1, reduced the protective effect of Nrf1 overexpression on OGD/R-induced TEC oxidative stress and pyroptosis. The results of this study, therefore, suggest that the inhibition of miR-92a-3p could alleviate TEC oxidative stress and pyroptosis by targeting Nrf1 in renal IRI.